P2X7 Activation Enhances Lipid Accumulation During Adipocytes Differentiation Through Suppressing the Expression of Sirtuin-3, Sirtuin-5, and Browning Genes - Chiang, Chien-Hsieh; Cheng, Ching-Yuan; Lien, Yi-Ting; Huang, Kuo-Chin; Lin, Wan-Wan (Frontiers in Pharmacology, 2022)
P2X7 signaling has been explored in adipose tissue because of its potential to promote ATP-activated inflammatory cascades during obesogenic environments. However, limited literature has investigated the role of the P2X7 receptor in lipid metabolism during adipocyte differentiation. This study sought to explore the regulatory roles of P2X7 in adipocytes. This study utilized the in vitro 3T3-L1 differentiation model. Lipid accumulation, intracellular triglyceride, and extracellular glycerol were determined. The selective P2X7 agonist BzATP and antagonist A438079 were administered to investigate the functions of P2X7. We found that the expression of P2X7 and the lipid accumulation increased during adipocyte differentiation from D0 to D4. When administered at D0/D2, A438079 attenuated, while BzATP enhanced the degree of lipid accumulation during adipocyte differentiation. Neither did BzATP and A438079 administration affect the expression of PPARγ and C/EBPα genes at D4. In addition, both intracellular triglyceride and extracellular glycerol levels at D4 were reduced by A438079 treatment and enhanced by BzATP administration. When administered at stage 2 of adipocyte differentiation, BzATP consistently enhanced lipid accumulation and intracellular TG and extracellular glycerol levels without affecting mRNA and protein levels of PPARγ and C/EBPα at D4. However, treating A438079 or BzATP at D4 did not affect intracellular TG formation and extracellular glycerol release in differentiated adipocytes at D7. Notably, BzATP administration at stage 2 exerted a concentration-dependent inhibition on the enhanced expression of PRDM16, PGC-1α, and UCP-1 at D4. Furthermore, BzATP administration at D0/D2 inhibited the protein and mRNA levels of sirtuin-3/5 at D4. BzATP treatment at stage 2 also suppressed the mRNA levels of sirtuin-3/5 genes upregulated by insulin. In conclusion, this study demonstrated P2X7 enhances lipid accumulation during adipogenesis by suppressing the expression of sirtuin-3/5 and the browning genes.